Man-made mineral fibers and lung cancer. Epidemiologic evidence regarding the causal hypothesis. - Miettinen, O. S.; Rossiter, C. E. (Scandinavian Journal of Work, Environment & Health, 1990)
Reviews of the epidemiologic literature point to a causal connection between lung cancer and exposure to airborne man-made mineral fibers. The present critical re-review starts with the requirements for epidemiologic evidence to be informative regarding a hypothesis on cancer etiology. The previous reviews relate lung cancer mortality to exposure that is too recent to be relevant. The relation to relevant (distant) exposure in the available data involves notable confounding by coexposure to other agents in the work environment, by the lower socioeconomic status of the exposed workers, and possibly by smoking. Moreover, analyses of trends in standardized mortality ratios according to timing and duration of exposure involve a lack of mutual comparability between the ratios. Given these problems, the available evidence is inadequate for testing the causal hypothesis. However, reanalyses of the available data, augmentation of the data with reanalyses, and new studies could eliminate the existing inadequacies.